Research on proposals and trends in the architectures of semantic search engines: A systematic literature review - Morales, J.; Sasieta, A. (Institute of Electrical and Electronics Engineers, 2017)
Semantic web technologies have gained some spotlight in recent years, mostly explained by the spread of mobile devices and broadband Internet access. As once envisioned by Tim Berners-Lee, semantic web technologies have fostered the development of standards that enable, in turn, the emergence of semantic search engines that give users the information they are looking for. This paper presents the results of a systematic literature review that focuses on understanding the proposals on the semantic search engines from an architectural point of view. From the results it is possible to say that most of the studies propose an integral solution for their users where their requirements, the context and the modules that comprise the search engine have a great role to play. Ontologies and knowledge also play an important role in these architectures as they evolve, enabling a great myriad of solutions that respond in a better way to the users' expectations.
Keywords: Computer science; Information retrieval; Data science; Semantic search; Search engine; World Wide Web; https://purl.org/pe-repo/ocde/ford#2.02.01